Renal hemodynamic effects differ between antidiabetic combination strategies: randomized controlled clinical trial comparing empagliflozin/linagliptin with metformin/insulin glargine - Ott, Christian; Jung, Susanne; Korn, Manuel; Kannenkeril, Dennis; Bosch, Agnes; Kolwelter, Julie; Striepe, Kristina; Bramlage, Peter; Schiffer, Mario; Schmieder, Roland (Cardiovascular Diabetology, 2021)
Background: Type 2 diabetes causes cardio-renal complications and is treated with different combination therapies. The renal hemodynamics profile of such combination therapies has not been evaluated in detail. Methods: Patients (N = 97) with type 2 diabetes were randomized to receive either empagliflozin and linagliptin (E+L group) or metformin and insulin glargine (M+I group) for 3 months. Renal hemodynamics were assessed with para-aminohippuric acid and inulin for renal plasma flow (RPF) and glomerular filtration rate (GFR). Intraglomerular hemodynamics were calculated according the Gomez´ model. Results: Treatment with E+L reduced GFR (p = 0.003), but RPF remained unchanged (p = 0.536). In contrast, M+I not only reduced GFR (p = 0.001), but also resulted in a significant reduction of RPF (p < 0.001). Renal vascular resistance (RVR) decreased with E+L treatment (p = 0.001) but increased with M+I treatment (p = 0.001). The changes in RPF and RVR were different between the two groups (both padjust < 0.001). Analysis of intraglomerular hemodynamics revealed that E+L did not change resistance of afferent arteriole (RA) (p = 0.116), but diminished resistance of efferent arterioles (RE) (p = 0.001). In M+I group RA was increased (p = 0.006) and RE remained unchanged (p = 0.538). The effects on RA (padjust < 0.05) and on RE (padjust < 0.05) differed between the groups. Conclusions: In patients with type 2 diabetes and preserved renal function treatment with M+I resulted in reduction of renal perfusion and increase in vascular resistance, in contrast to treatment with E+I that preserved renal perfusion and reduced vascular resistance. Moreover, different underlying effects on the resistance vessels have been estimated according to the Gomez model, with M+I increasing RA and E+L predominantly decreasing RE, which is in contrast to the proposed sodium-glucose cotransporter 2 inhibitor effects. Trial registration: The study was registered at www.clinicaltrials.gov (NCT02752113) on April 26, 2016
CRIS-Team Scopus Importer:2021-09-17
Keywords: Hemodynamics; Intraglomerular; Renal; Type 2 diabetes